Pengaruh Perputaran Modal Kerja, Inflasi dan BI-7 Day Reverse Repo Rate terhadap Harga Saham pada Industri Konstruksi Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020 - Larasati Kusumo Wardani (Universitas Batanghari Jambi, 2022)
The aim of this research is to analyze the influence of Working Capital Turnover, Inflation and BI-7 Day Reverse Repo Rate on Stock Prices. The author draws the hypothesis that Exchange Working Capital Turnover, Inflation and the BI-7 Day Reverse Repo Rate have a positive and significant effect on stock prices.The research methodology used is descriptive analysis method and statistical analysis method. The analytical tool used is multiple linear regression analysis. The data used is secondary data. Hypothesis testing was carried out using the F test and t test, with a significance level (α) of 5%. Data analysis used statistical data processing software, namely SPSS version 25 for Windows.This research was conducted during the 2017-2021 period. The results of the F test show that the Exchange Working Capital Turnover, Inflation and the BI-7 Day Reverse Repo Rate have a positive and significant effect on stock prices. The results of the t test (individually) show that the Working Capital Turnover variable has a positive and significant effect on stock prices. The results of the coefficient of determination in this study amounted to 0.250. This means that the Stock Price Index is influenced by the Exchange Working Capital Turnover, Inflation and the BI-7 Day Reverse Repo Rate.